PENALA PARAMETER PID OTOMATIS PADA PENGATUR KECEPATAN MOTOR INDUKSI TIGA FASA - Handri Toar; Era Purwanto; Hary Oktavianto; Ridwan Ridwan; Muhammad Rizani Rusli (JURNAL INTEGRASI, 2020)
PID is one of the simple controller, fast computing, easy to implement, reliable to face the disturbance especially to handle the linear system. Meanwhile induction motor is one of a high nonlinear system. Is PID can handle the induction motor. Therefore PID controller enhancement is needed. The controller has the ability to tune up the parameter while running. To tune-up, the controller needs a bunch of collections of parameters PID that ready to use. If we use the manual way to collect like trial and error, it will consume much power and time. And not all systems can be used the Ziegler-Nichols method. This research offering an algorithm for the autotuning PID parameter to control the speed of induction motor based on vector control to collect the PID parameter automatically. After validation by using LabVIEW simulation, the system provides a good speed response without overshoot when the speed increased and without undershoot when the speed decreased.